WHO global vaccine safety multi-country collaboration project on safety in pregnancy: Assessing the level of diagnostic certainty using standardized case definitions for perinatal and neonatal outcomes and maternal immunization. (December 2021) - Stuurman, Anke L.; Sharan, Apoorva; Jahagirdar, Shubhashri; Elango, Varalakshmi; Riera-Montes, Margarita; Kashyap, Neeraj; Biccler, Jorne; Poluru, Ramesh; Arora, Narendra; Mathai, Matthews; Mangtani, Punam; DeVlieger, Hugo; et al.
Highlights: Applicability of GAIA definitions were assessed using medical records in LMICs. LBW, preterm birth and neonatal death definitions were applicable in the field. SGA, stillbirth, neonatal infection, congenital microcephaly definitions were less applicable. Suggestions to the improvement in GAIA definitions were made. Better documentation of maternal immunization is suggested for vaccine-safety studies. Abstract: Standardized case definitions strengthen post-marketing safety surveillance of new vaccines by improving generated data, interpretation and comparability across surveillance systems. The Global Alignment of Immunization Safety Assessment in Pregnancy (GAIA) project developed standardized case definitions for 21 key obstetric and neonatal terms following the Brighton Collaboration (BC) methodology. In this prospective cohort study, we assessed the applicability of GAIA definitions for maternal immunization exposure and for low birth weight (LBW), preterm birth, small for gestational age (SGA), stillbirth, neonatal death, neonatal infection, and congenital microcephaly. We identified the missing data elements that prevented identified cases and exposures from meeting the case definition (level 1–3 of BC diagnostic certainty). Over a one-year period (2019–2020), all births occurring in 21 sites (mostly secondary and tertiary hospitals) in 6 Low Middle Income Countries and 1 High Income Country were recorded and the 7 perinatal and neonatal outcome cases were identified from routine medical records. Up to 100 cases per outcome were recruited sequentially from each site. Most cases recruited for LBW, preterm birth and neonatal death met the GAIA case definitions. Birth weight, a key parameter for all three outcomes, was routinely recorded at all sites. The definitions for SGA, stillbirth, neonatal infection (particularly meningitis and respiratory infection) and congenital microcephaly were found to be less applicable. The main barrier to obtaining higher levels of diagnostic certainty was the lack of sonographic documentation of gestational age in first or second trimester. The definition for maternal immunization exposure was applicable, however, the highest level of diagnostic certainty was only reached at two sites. Improved documentation of maternal immunization will be important for vaccine safety studies. Following the field-testing of these 8 GAIA definitions, several improvements are suggested that may lead to their easier implementation, increased standardization and hence comparison across studies.